Literature Review: Analysis of Articles on the Application of the Discovery Learning Method in Indonesian Language Learning to Improve Reading Comprehension Skills of Elementary School Students - Yolanda, Yolanda; Pebriana, Putri Hana; Saputra, Indra; Ningsih, Siska Kartika; Mulyani, Siti; Azzahra, Ghiatsya (The Future of Education Journal, 2025)
The Discovery Learning (DL) paradigm is a learning approach that encourages students to independently discover knowledge and concepts through active engagement in the learning process. This approach has been widely applied in various teaching methods, particularly in Indonesian language learning. However, traditional teaching methods, such as lectures, are still frequently used in many classrooms, where the teacher plays a dominant role and minimally involves students actively. As a result, students lose interest and enthusiasm for the material being taught and are less engaged in the learning process.The implementation of the Discovery Learning model provides opportunities for students to be more active in the learning process, thereby supporting the successful achievement of learning objectives. This study aims to analyze how the Discovery Learning approach can improve elementary school students' reading comprehension skills. The approach used in this research is a literature review of previous studies published in the last five years.A total of 15 relevant articles were collected and analyzed to gain insights into the effectiveness of this learning model. The results of the review indicate that Discovery Learning can enhance student engagement, build better reading comprehension, and increase students' interest in learning. Therefore, Discovery Learning is an effective learning model to be applied in Indonesian language learning at the elementary school level.